Optimal Parameters Synthesis of Biodiesel From Frying Oils Wastes - Soulayman, Soulayman; Dayoub, Ola (International Journal of Renewable Energy Development, 2019)
This study is devoted to produce biodiesel from recycled wastes frying oils (WFO) using commercial grade chemicals in an attempt to help reducing the cost of biodiesel and pollution coming from WFO. The base – catalyzed transesterification method was applied. The variables affecting the yield and characteristics of the biodiesel produced from WFO were studied. Sodium hydroxide is used as catalyst. Different reaction times, different methanol/WFO volume ratios and different catalyst/WFO weight ratios were used with purpose of achieving the best conditions for biodiesel production A series of experiments were carried out, using methanol/WFO volume ratios from 10% to 30% and catalyst/WFO weight ratio from 0.2% to 0.8%. It was found that in treating WFO which contains 0.12% of water by weight and having an acid value of 0.52 mg of KOH/g of oil, and an iodine value 130.42 gI/100 g of oil, no need in acidic pretreatment.  Moreover, it was found that, for WFO with an acidic value of 0.52 mg KOH/gWFOs, results show that a methanol/WFO volume ratio of 13% and a catalyst/WFO weight ratio of 0.4% give the highest yield of methyl esters.  A pilot production unit of 400l/day of production capacity was designed and constructed on the basis of laboratory experiments and the process was verified on the pilot scale.©2019. CBIORE-IJRED. All rights reservedArticle History: Received October 18th 2017; Received in revised form May 17th 2018; Accepted December 8th 2018; Available onlineHow to Cite This Article: Soulayman, S. and Ola, D. (2019) Synthesis Parameters of Biodiesel From Frying Oils Wastes. Int. Journal of Renewable Energy Development, 8(1), 33-39.https://doi.org/10.14710/ijred.8.1.33-39